Interorgan communication with the liver: novel mechanisms and therapeutic targets - Zhao, Jiulu; Zhang, Xi; Li, Yuan; Yu, Jizhang; Chen, Zhang; Niu, Yuqing; Ran, Shuan; Wang, Song; Ye, Weicong; Luo, Zilong; Li, Xiaohan; Hao, Yanglin; et al. (Frontiers in Immunology, 2023)
The liver is a multifunctional organ that plays crucial roles in numerous physiological processes, such as production of bile and proteins for blood plasma, regulation of blood levels of amino acids, processing of hemoglobin, clearance of metabolic waste, maintenance of glucose, etc. Therefore, the liver is essential for the homeostasis of organisms. With the development of research on the liver, there is growing concern about its effect on immune cells of innate and adaptive immunity. For example, the liver regulates the proliferation, differentiation, and effector functions of immune cells through various secreted proteins (also known as "hepatokines"). As a result, the liver is identified as an important regulator of the immune system. Furthermore, many diseases resulting from immune disorders are thought to be related to the dysfunction of the liver, including systemic lupus erythematosus, multiple sclerosis, and heart failure. Thus, the liver plays a role in remote immune regulation and is intricately linked with systemic immunity. This review provides a comprehensive overview of the liver remote regulation of the body's innate and adaptive immunity regarding to main areas: immune-related molecules secreted by the liver and the liver-resident cells. Additionally, we assessed the influence of the liver on various facets of systemic immune-related diseases, offering insights into the clinical application of target therapies for liver immune regulation, as well as future developmental trends.